Associations between continuous glucose monitoring-derived metrics and diabetic retinopathy and albuminuria in patients with type 2 diabetes - Hirotaka Watada; Tomoya Mita; Takeshi Osonoi; Masahiko Gosho; Iichiro Shimomura; Toshihiko Shiraiwa; Yosuke Okada; Satomi Wakasugi; Naoto Katakami; Hidenori Yoshii; Keiko Nishida; Keiichi Torimoto; et al. (BMJ Open Diabetes Research & Care)
Introduction Preventing the development and progression of diabetic microvascular complications through optimal blood glucose control remains an important challenge. Whether metrics based on continuous glucose monitoring are useful for the management of diabetic microvascular complications is not entirely clear.Research design and methods This is an exploratory analysis of an ongoing prospective, multicenter, 5-year follow-up observational study. Study participants included 999 outpatients with type 2 diabetes who underwent continuous glucose monitoring at baseline. Associations between continuous glucose monitoring-derived metrics and the severity of diabetic retinopathy or albuminuria were investigated using multivariable proportional odds models.Results The overall prevalence of diabetic retinopathy was 22.2%. Multivariate analysis with proportional odds models demonstrated that continuous glucose monitoring-derived metrics related to intraday and interday glucose variability are significantly associated with the severity of diabetic retinopathy, even after adjusting for various possible risk factors. However, significant relationships were not observed after adjusting for hemoglobin A1c (HbA1c) levels. The prevalence of microalbuminuria and macroalbuminuria was 20.3% and 6.7%, respectively. Similarly, multivariate analysis demonstrated that those metrics are significantly associated with the severity of albuminuria. These relationships remained significant even after further adjusting for HbA1c levels.Conclusions Continuous glucose monitoring-derived metrics related to intraday and interday glucose variability are significantly associated with the severity of diabetic retinopathy or albuminuria in patients with type 2 diabetes. Thus, evaluating these metrics might possibly be useful for risk assessment of diabetic microvascular complications.Trial registration number UMIN000032325.